2015
DOI: 10.1186/s13071-015-0700-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of repeated NeemAzal®-treated blood meals on the fitness of Anopheles stephensi mosquitoes

Abstract: BackgroundHerbal remedies are widely used in many malaria endemic countries to treat patients, in particular in the absence of anti-malarial drugs and in some settings to prevent the disease. Herbal medicines may be specifically designed for prophylaxis and/or for blocking malaria transmission to benefit both, the individual consumer and the community at large. Neem represents a good candidate for this purpose due to its inhibitory effects on the parasite stages that cause the clinical manifestations of malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…This molecule interferes with the endocrine system by impairing juvenile hormone (JH) and 20‐hydroxyecdysone (20E) pathways, which are involved in the regulation of many physiological functions . Thus azadirachtin induces growth and moulting abnormalities and can cause significant alterations in the reproductive system of both male and female insects, including ovarian and testes development, fecundity, fertility, oviposition and egg viability . Azadirachtin also shows moderate to strong cytotoxicity, neurotoxicity and antimitotic effects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule interferes with the endocrine system by impairing juvenile hormone (JH) and 20‐hydroxyecdysone (20E) pathways, which are involved in the regulation of many physiological functions . Thus azadirachtin induces growth and moulting abnormalities and can cause significant alterations in the reproductive system of both male and female insects, including ovarian and testes development, fecundity, fertility, oviposition and egg viability . Azadirachtin also shows moderate to strong cytotoxicity, neurotoxicity and antimitotic effects .…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus azadirachtin induces growth and moulting abnormalities and can cause significant alterations in the reproductive system of both male and female insects, including ovarian and testes development, fecundity, fertility, oviposition and egg viability. 9,12,[30][31][32] Azadirachtin also shows moderate to strong cytotoxicity, neurotoxicity and antimitotic effects. 9,33,34 It acts on the expression of genes related to development in Drosophila melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos apontam atividade favorável em bloquear a ação de vetores como Anopheles coluzzii na transmissão do Plasmodium falciparum (Yerbanga et al,2014). Bem como ação anti-vetorial sobre o Anopheles stephensi, que é considerado um dos principais transmissores da malária (Dembo et al, 2015).…”
Section: Resultsunclassified
“…In fact, a substantial number of studies conducted with neem extracts, limonoid enriched preparations or purified azadirachtin report ovicidal, larvicidal, adulticidal, anti-feedant, and repellent properties against different mosquito vectors [ 17 – 23 ]. For example, a recent study by a coauthor of the present work showed an impact of NeemAzal ® (a commercial methanol extract from seed kernels of A. indica rich in azadirachtin A, the major bioactive compound) on the blood volume intake of Anopheles stephensi after repeated feeding on mice treated with the product at an azadirachtin concentration of 60–150 mg/kg [ 24 ]. After the 5th blood meal at the highest dosage, mosquitoes’ oviposition was reduced by 50–65 % and egg hatchability by 70 %.…”
Section: Introductionmentioning
confidence: 99%
“…After the 5th blood meal at the highest dosage, mosquitoes’ oviposition was reduced by 50–65 % and egg hatchability by 70 %. [ 24 ]. The possible activity of neem extracts on tsetse fly biology has, to our knowledge, never been explored.…”
Section: Introductionmentioning
confidence: 99%